Beekeeping in Manicaland Province and Lessons for Poverty Reduction - Muridzi, Gibson (My University, 2013)
The research examined beekeeping in Manicaland Province in Zimbabwe and identified lessons on poverty reduction. Quantitative research methods were used to enhance knowledge and understanding by objectively investigating the outcomes of beekeeping projects in the province. The main findings of the research were that beekeeping projects have limited impact in reducing poverty in rural communities as the projects are on a small scale basis, as evidenced by the number of beehives each farmer has. The Queen Bee breeding programme is not being fully utilised by farmers to increase the output or production of honey. Farmers do not have apiaries on their farms and are not promoting biodiversity through orchards or plantations on their farms. Donors support farmers with farm inputs as a way of providing forage for the bees. However, the assistance of donors is hampered by low rainfall in province.
MM (P&DM) thesis
Keywords: Beekeeping; Poverty reduction